A Taxonomical Study on the Rotifera Fauna in Pertek Region of Keban Dam Lake - Tellioglu, Ayda; Akman, Fatih (Ege Univ, 2007)
In this study, the Rotifera fauna in Pertek region of Keban Dam Lake was taxonomically investigated between August 2002 and July 2003. Twenty species belonging to the phylum Rotifera were identified, six of which Polyarthra remata, Asplanchna sieboldi, Hexarthra mira, Hexarthra fennica, Testudinella patina and Trichocerca cylindrica were new for this lake.
Keywords: Rotifera; zooplankton; taxonomy; Keban Dam Lake